Peningkatan Keterampilan Berbicara Bahasa Jerman Melalui Media Video Hallo Aus Berlin - Elsita Lisnawati; Muh. Anwar (Universitas Negeri Makassar, 2022)
Abstract. This research is Classroom Action Research (CAR) which consists of two cycles. This study aims to determine the planning, process, and results of the Hallo aus Berlin video learning media in improving the German speaking skills of students in class XI MIA 5 SMA Negeri 9 Makassar. The data of this study consisted of quantitative and qualitative data. Quantitative data was obtained through the results of the speaking skills test in cycle I and cycle II and qualitative data was obtained through observation. The data were analyzed using the percentage technique. The results showed that the average score obtained by students in the first cycle reached 70% and the second cycle reached 83%. These results indicate that the use of video learning media Hallo aus Berlin improves the German speaking skills of students in class XI MIA 5 SMA Negeri 9 Makassar.Keywords: Video Hallo aus Berlin, Speech Skills, German